KAJIAN PENERAPAN MEKANISASI PERTANIAN DI LAHAN RAWA LEBAK DESA PUTAK - MUARA ENIM - Djamhari, Sudaryanto (Badan Pengkajian dan Penerapan Teknologi, 2009)
The industrial and population growth in Java leads to converse the land function from the agriculture to industrial, estate and high way. Therefore, the development of agriculture must be relocated to outside Java, where there are a lot of land available. One agricultural of problems in outsideJava is the lack of labour especially for land cultivation and other which need many labour.The use of mechanical appliance. is the best alternative to overcome that problem. This research was assessed four aspects for applying of mechanical appliance in lebak bog farm. The objective of the research was to extend the use mechanical appliance to increase farm production, farmer income and tractor interpreneur income.